Modellbasierte Prozesskettenabbildung rührreibgeschweißter Aluminiumhalbzeuge zur umformtechnischen Herstellung höchstfester Leichtbaustrukturteile - Gnibl, Tobias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)
A key factor for an efficiency increase in air plane and space ship manufacturing is the development of technologies for cost and resource efficient production of structural parts. High strength aluminum alloys show a high potential for the use in aerospace applications, nevertheless innovations are limited by the state of the art of shaping technologies. An advanced approach is to form large scale spherical parts from tailor welded blanks. Therefor it is essential to have the knowledge about the interactions along the process chain and be able to calculate their influence on final part properties and quality. Within this scientific work specific material characterization provides the basis for the understanding of heat treatment, forming and joining technology. Furthermore, to be able to fulfill multi criteria specifications in part and process design a methodology based on analytical and numerical models has been introduced and verified according its general applicability for the manufacturing of light-weight structural parts made of high strength aluminu